Mergers and Acquisitions in Latin America: Industrial Productivity and Corporate Governance (2016)
This paper examines the impact of industrial productivity on transnationals M&As from OECD countries towards Latin American countries in the period 1996 to 2010. It also analyzes the relationship between external mechanism of corporate governance and transnational M&As. For this purpose we use a gravitational model at the industry level. We find that industry productivity and higher standards of corporate governance in the country of origin promote transnational M&As activity. However, it is also found that higher levels of capital and technological productivity decreases transnational M&As activity.